Action Research in International Educational Settings: Bridging the Gap at the American University of Bulgaria - Mari Firkatian; Sandy Feinstein (Networks: An Online Journal for Teacher Research, 2002)
As articulated by Yolanda Wadsworth, our use of the word "research" would be a misnomer (Wadsworth, 1998). After all, this article does not even involve what might pass for qualitative research, nor is it intended to serve as an example of research. Rather, it describes an incipient phase of research: observation and description. We are sharing our hypothesis, though our fieldwork is not systematic; we are offering a retrospective, partly impressionistic glance at an experience in an attempt to prepare for future comparative research as well as the developing of pedagogies based on experience. While not adhering to a scientific methodology that would qualify as bona fide research, we have "come to understand the practical and ethical implications" of what Wadsworth goes on to enumerate: "the effects of raising some questions and not others; the effects of involving some people in the process [or even apparently only one] and not others; the effects of observing some phenomena and not others; the effects of making this sense of it and not alternative senses, and the effects of deciding to take this action [or no action] as a result of it rather than any other action and so on." These distinctions are important to us, for they partly resolve the issues of contradiction in research raised by Pam Swepson (1998).